Dental Caries and Salivary Mutans Streptococci Level among a Group of Mothers and their Children in Relation to Feeding (Mustansiria Dental Journal, 2018)
Dental caries is the most prevalent oral disease among children and young adults which is caused mainly by mutans streptococci. The relation of dental caries and salivary mutans streptococci between children and their mothers according to the type of child feeding was controversies.A sample of 56 child-mother pairs with age range for children 3-4 year old and 25-30 year old for their mothers were examined. Dental caries was recorded following the WHO (1987) criteria. The Mitis Salivarius Bacitracin Agar was used for the cultivation of mutans streptococci.None significant difference was found in dental caries and salivary mutans streptococci between the breast and bottle fed children (P>0.05). The percentage of caries free breast fed children was higher than that of the bottle fed children. Highly significant positive strong correlations were found between both groups of children and their mothers regarding dental caries experience and salivary mutans streptococci count.The mother plays an important role in transferring salivary mutans streptococci and as a results dental caries to her child regarding both type of child feeding.